2019
DOI: 10.1016/j.hpb.2018.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Impact of expanding indications on surgical and oncological outcome in 1434 consecutive pancreatoduodenectomies

Abstract: Background: Over the years, high-volume pancreatic centers expanded their indications for pancreatoduodenectomy (PD) but with unknown impact on surgical and oncological outcome.Methods: All consecutive PDs performed between 1992-2017 in a single pancreatic center were identified from a prospectively maintained database and analyzed according to three time periods. Results: In total, 1434 patients underwent PD. Over time, more elderly patients underwent PD (P < 0.001) with increased use of vascular resection (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 52 publications
3
13
0
Order By: Relevance
“…The incidence of pancreatic ductal adenocarcinoma and periampullary cancer has increased over the past two decades, resulting in increasing numbers of patients amenable for cancer-directed treatment 1 . Pancreatic surgery in combination with systemic chemotherapy provides the best outlook for long-term survival, but is associated with a relatively high risk of complications [2][3][4] . Studies [5][6][7] have demonstrated a clear relationship between hospital volume and postoperative mortality.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of pancreatic ductal adenocarcinoma and periampullary cancer has increased over the past two decades, resulting in increasing numbers of patients amenable for cancer-directed treatment 1 . Pancreatic surgery in combination with systemic chemotherapy provides the best outlook for long-term survival, but is associated with a relatively high risk of complications [2][3][4] . Studies [5][6][7] have demonstrated a clear relationship between hospital volume and postoperative mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown an increase of VR over the time, indicating that there should be sufficient exposure in the training program of pancreatoduodenectomy surgeons. [36][37][38] Most surgeons thought that Type 4 reconstruction carried the highest risk of complications. Several studies about association between type of VR and complications exist.…”
Section: Discussionmentioning
confidence: 99%
“…pancreascalculator.com. A systematic review including 9 monocenter series of at least 500 consecutive PDs, 19 found a rate of DGE of 8.6%-18.0% in studies with PD performed for all indications. [20][21][22][23][24][25] The rate of DGE grade B/C after PD in this cohort was 26.9% and thus on the higher side of this range.…”
Section: Discussionmentioning
confidence: 99%